2019
DOI: 10.12911/22998993/94919
|View full text |Cite
|
Sign up to set email alerts
|

Recyclability of Ore Beneficiation Wastes at the Lomonosov Deposit

Abstract: The Lomonosov diamond mine is located in the Primorsky district of the Arkhangelsk region, 100 km northeast from the Arkhangelsk and is represented by six kimberlite pipes: Pomorskaya, Arkhangelskaya, Karpinsky-1, Karpinsky-2, Pionerskaya, and Lomonosov. Ore mining has been carried out since 2005 on the Arkhangelskaya pipe located in the southern part of the deposit. The Arkhangelskaya pipe is composed of tuffites, tuffaceous sandstones, breccias of sedimentary rocks, and sandstones. The kimberlite mineral com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 6 publications
(6 reference statements)
0
6
0
Order By: Relevance
“…However, the environmental and economic calculations showed that this technological solution requires significant capital expenditures, as well as a large amount of time for creating a new tailing dump. It makes the implementation of such a project economically unfeasible today [Pashkevich et al 2019].…”
Section: Resultsmentioning
confidence: 99%
“…However, the environmental and economic calculations showed that this technological solution requires significant capital expenditures, as well as a large amount of time for creating a new tailing dump. It makes the implementation of such a project economically unfeasible today [Pashkevich et al 2019].…”
Section: Resultsmentioning
confidence: 99%
“…We studied 13 bulk samples and the corresponding thin sections, zircon single fraction from 8 samples of biotite granites (more than 555 grains), and 5 samples of zinnwaldite Li-F granites (460 grains). The studies were conducted in the laboratories of the Mining University [18][19][20], the Russian Geological Research Institute (VSEGEI), the Institute of Precambrian Geology and Geochronology, the Russian Academy of Sciences (Saint Petersburg, Russia), and the Institute of Mineralogy, TU Bergakademie Freiberg (Freiberg, Germany) (Table 2).…”
Section: Methodsmentioning
confidence: 99%
“…As part of the technological equipment of oil terminals, a common solution is Vapor Recovery Units (VRU) (Mulder, 2007). However, the introduction of such units in emerging economies is rare (Pashkevich and Petrova, 2019). This is due to the following reasons: significant cost, high (in some cases) energy intensity, long payback period, and minor legal restrictions (Litvinenko, 2020).…”
Section: Introductionmentioning
confidence: 99%